Acidic Deep Eutectic Solvent as a Catalyst for the Esterification of Levulinic Acid to Ethyl Levulinate - Jamarudin, Aizah; Zainol, Muzakkir Mohammad; Hassan, Abdull Hafidz; Ismail, Siti Norazian; Asmadi, Mohd; Zainuddin, Kamarul Ridwan; Yusof, Nurul Asyikin; Anggoro, Didi Dwi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Deep eutectic solvents (DESs) are environmentally friendly compounds that can be synthesized through the combination of hydrogen-bond donors and acceptors. The diverse applications of DESs underscore their potential as catalysts in various chemical reactions. In this study, an acidic DES was prepared as a catalyst for levulinic acid (LA) esterification with ethanol to produce ethyl levulinate (EL). The acidic DES was prepared from choline chloride and sulfanilic acid through thermal mixing. Characterization of the DES was conducted using Fourier transform infrared-attenuated total reflectance and nuclear magnetic resonance spectroscopy analysis to identify its functional groups and confirm the structure. Additionally, the thermal stability of the DES was analyzed using thermogravimetric analysis, while its acidity was determined using acid-base titration. The esterification of LA with ethanol was assessed under reflux conditions at 80 °C, with specific parameters examined: the molar ratio of LA to ethanol (ranging from 1:5 to 1:13), the ratio of LA to DES (ranging from 1:0.4 to 1:1.4), and the reaction duration (0.5–5 h). The DES used in this work showed an acidity of 2.89 mmol/g. The optimum conditions were obtained at a 1:7 molar ratio of LA to ethanol, a 1:1.2 ratio of LA to DES, and 3 h of reaction time at 80 °C, resulting in 99% conversion of LA to EL. This finding highlights the remarkable catalytic performance of the choline chloride/sulfanilic acid DES in facilitating a highly efficient conversion of LA to EL. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).